1978
DOI: 10.1254/jjp.28.61
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Studies on Physiological and Pharmacological Actions of L-Ascorbate 2-Sulfate. V. On the Hypolipidemic and Anti Atherosclerotic Effects of L-Ascorbate 2-Sulfate in Rabbits

Abstract: The area rate of atheromatous plaque in aorta was less in specimens from both groups of AAS than in those from control I. Pathological changes in intima and media of aorta were milder in specimens from both groups of AAS.Development of pathological changes in arteries of various organs were prevented with both doses of AAS.The hypocholesterolemic effects of L-ascorbate 2-sulfate (AAS) in mice and rats have been reported in a previous paper (1) in which we suggested that AAS is a prospective hypolipidernic drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…It was reported that AAS has hypolipidemic effects in normal rats in a dose of 250mg/kg, in cholesterol-fed rats and rabbits in doses of 150 and 300mg/kg, and in cholesterol-fed guinea pigs at a dose of 300mg/kg, respectively (4)(5)(6). In this experiments, AAS was effective at a dose of 300 mg/kg on fatty liver and/or hyperlipidemia induced by various treatments (Tables 2 and 5).…”
Section: Discussionsupporting
confidence: 55%
“…It was reported that AAS has hypolipidemic effects in normal rats in a dose of 250mg/kg, in cholesterol-fed rats and rabbits in doses of 150 and 300mg/kg, and in cholesterol-fed guinea pigs at a dose of 300mg/kg, respectively (4)(5)(6). In this experiments, AAS was effective at a dose of 300 mg/kg on fatty liver and/or hyperlipidemia induced by various treatments (Tables 2 and 5).…”
Section: Discussionsupporting
confidence: 55%
“…Analyses of lipids and AA: Analysis of lipids in serum and liver were carried out as described in the previous papers (6,7). AA in various organs was extracted by homo genization with 1.4N acetic acid in 6 % metaphosphoric acid and centrifuging at 3,000 rpm for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…We reported in previous papers that AAS exerts lipid lowering effects in experimental hyperlipidemia with mice, rats and rabbits, and prevents development of atherosclerosis (6,7). In an attempt to dissociate the effect of AAS from that of L-ascorbic acid (AA), the present study of AAS on lipid metabolism has been carried out in guinea pigs which do not to biosynthesize AA in vivo.…”
Section: L-ascorbatementioning
confidence: 99%